Nonrelativistic ferromagnetotriakontadipolar order and spin splitting in hematite - X. H. Verbeek; D. Voderholzer; S. Schären; Y. Gachnang; N. A. Spaldin; S. Bhowal (Physical Review Research)
We show that hematite, α-Fe_{2}O_{3}, below its Morin transition, has a ferroic ordering of rank-5 magnetic triakontadipoles on the Fe ions. In the absence of spin-orbit coupling, these are the lowest-order ferroically aligned magnetic multipoles, and they give rise to the g-wave nonrelativistic spin splitting in hematite. We find that the ferroically ordered magnetic triakontadipoles result from the simultaneous antiferroic ordering of the charge hexadecapoles and the magnetic dipoles, providing a route to manipulating the magnitude and the sign of the magnetic triakontadipoles as well as the spin splitting. Furthermore, we find that both the ferroic ordering of the magnetic triakontadipoles and many of the spin-split features persist in the weak ferromagnetic phase above the Morin transition temperature.